2020
DOI: 10.1093/brain/awaa361
|View full text |Cite
|
Sign up to set email alerts
|

Retinal asymmetry in multiple sclerosis

Abstract: The diagnosis of multiple sclerosis is based on a combination of clinical and paraclinical tests. The potential contribution of retinal optical coherence tomography (OCT) has been recognized. We tested the feasibility of OCT measures of retinal asymmetry as a diagnostic test for multiple sclerosis at the community level. In this community-based study of 72 120 subjects, we examined the diagnostic potential of the inter-eye difference of inner retinal OCT data for multiple sclerosis using the UK Biobank data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 47 publications
3
33
0
Order By: Relevance
“…Recent studies have shown intereye difference for pRNFL and mGCIPL can contribute to identifying unilateral optic nerve lesions and this may represent supportive measures for MS diagnosis ( Nolan et al, 2018 , Petzold et al, 2021 ). However, in the current study, the inter-eye absolute difference of pRNFL and mGCC did not improve the detection of MS from healthy controls as compared to the conventional approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown intereye difference for pRNFL and mGCIPL can contribute to identifying unilateral optic nerve lesions and this may represent supportive measures for MS diagnosis ( Nolan et al, 2018 , Petzold et al, 2021 ). However, in the current study, the inter-eye absolute difference of pRNFL and mGCC did not improve the detection of MS from healthy controls as compared to the conventional approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the current study, the inter-eye absolute difference of pRNFL and mGCC did not improve the detection of MS from healthy controls as compared to the conventional approach. The limited diagnostic accuracy of retinal asymmetry may be due to study designs (community sample vs clinical sample), patient profiles such as MS disease activity, or co-morbidities ( Petzold et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Percentage rather than absolute IOD may be superior over absolute IOD in detecting subtle changes 33 . Clinically meaningful cut-off values may be defined in comparison to healthy controls 20 or based on large reference studies with MS-derived OCT measures 32,34 . Machine learning based classification of eyes with ON history utilizing standard OCT parameters has been promising (Kenney et al in press ).…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of studies, GCIPL was described as a suitable predictive marker of visual function after ON and neurological deterioration, as measured by the EDSS [66][67][68]. Additionally, in a recently published study [69], the inter-eye difference in GCIPL thickness differentiated MS patients in a large community cohort not only from healthy subjects but also from patients with other diseases. However, there is no information concerning patients with NSWMLs.…”
Section: Discussionmentioning
confidence: 99%